Effects of the position of a bluff-body on the diffusion flames: A combined experimental and numerical study. (25th February 2018) - Tong, Yiheng; Liu, Xiao; Chen, Shuang; Li, Zhongshan; Klingmann, Jens
Highlights: Effects of position of bluff-body on flame patterns and instabilities are studied. A bluff-body outer wall-adjacent vortex enhances flame stabilization. Combustion enhances central jet penetration, enlarges air-driven vortex. Abstract: The effects of the position of a bluff-body on diffusion flame structures and flame instability characteristics were investigated both experimentally and numerically. The flame pattern diagram and the stability limits of the methane-air diffusion flame were investigated to evaluate the effects caused by the alternation of the position of a bluff-body. A disk-shape bluff-body was mounted 10 mm above or at the same height with the annular channel exit. The bulk velocity of the annular air flow varied between Ua  = 0 to 8 m/s; while the fuel jet velocity being ranged from Uj  = 0 to 30 m/s. Various flame patterns, including the recirculation zone flame, the stable diffusion flame, the split flame and the lifted flame till flame blowoff, were observed and recorded by the high-speed camera. High-speed Particle Image Velocimetry (PIV) was also adopted to give deeper insight into the characteristics of the flow fields and the flame patterns. The hybrid RANS/LES model was utilized to simulate the mixing characters of the reactants, the scalar dissipation rates, the flow fields and their interactions with the flame structures. The size and strength of the recirculation zones downstream of the bluff-body altered with the change in the position of the bluff-body. It is found that flames in burners with two different bluff-body positions behave similarly with each other, except those under conditions with high annular air velocities ( Ua  > 6.8 m/s). Mounting the bluff-body 10 mm above the annular channel exit could better stabilize the flame. A recirculation vortex was found adjacent to the outer wall of the bluff-body. It played an important role in the flame stabilization. Combustion affected the flow fields significantly by accelerating the central jet and enlarging the outer recirculation zone.